المسؤولية الجنائية الناشئة عن التعامل بالمخدرات والمؤثرات العقلية في التشريع الفلسطيني - Mohamed Salh Tayim; Hussein 'Azeemi Bin Abdullah Thidi; Syahirah Abdul Shukor (WorldConferences.net, 2024)
Volume: 7 (page 51 – 80)